Chemotherapy-Induced ECG Changes in HCC Patients - Kubekova, Saule; Rib, Yelena; Zagorulya, Natalya; Malayev, Niyaz; Biktashev, Damir; Kuanyshbayeva, Gaukhar; Ulbolssyn, Saltabayeva; Markabayeva, Akbayan; Bayanova, Dinara; Donayeva, Ainur (Bangladesh Journal of Medical Science, 2025)
According to Globocan, in 2022, the highest incidence of hepatocellular carcinoma (HCC) was observed in Asia, which accounted for 75% of the global burden of liver cancer 1. In the Republic of Kazakhstan in 2022, the incidence of liver cancer was 5.1 per 100,000 population, with a mortality rate of 2.9, respectively. For the period 2014-2022, HCC had the lowest five-year survival rate among all malignant neoplasms in Kazakhstan2,3. The treatment of HCC across various stages involves a range of clinical strategies4. Sorafenib is currently the primary drug in the treatment of HCC 4,5 and doxorubicin is used in transarterial hepatic artery chemoembolization (TACE)8. However, their use results in cardiotoxicity leading to cancer therapeutics-related cardiac dysfunction (CTRCD)9. CRTCD manifests as cardiovascular disease symptoms in patients with HCC, reflecting irreversible structural changes in the myocardium10. BJMS, Vol. 24 No. 04 October’25 Page : 1189-1196